2014
DOI: 10.4187/respcare.03350
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients With COPD Be Vaccinated?

Abstract: BACKGROUND: Exacerbations of COPD are a major component of the socioeconomic burden related to COPD, and frequent exacerbations are associated with greater decline in health status. Tracheobronchial infections are involved in 50 -70% of exacerbations, so influenza and pneumococcal vaccines are recommended for prevention. The aim of this study was to determine the level of knowledge among COPD patients about the vaccines, find the rate of patients inoculated with both influenza and pneumococcal vaccines, and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
23
1
1
Order By: Relevance
“…On the contrary, another study concluded that receiving vaccination was not related to the level of education but that the advice of health care professionals (particularly a doctor) led to high vaccination compliance [16]. Our findings showed that there was no relationship be- tween the level of education and status for vaccination.…”
Section: Discussioncontrasting
confidence: 54%
“…On the contrary, another study concluded that receiving vaccination was not related to the level of education but that the advice of health care professionals (particularly a doctor) led to high vaccination compliance [16]. Our findings showed that there was no relationship be- tween the level of education and status for vaccination.…”
Section: Discussioncontrasting
confidence: 54%
“…Other studies also point out that the advice of a health care professional (particularly a physician) leads to better vaccination compliance. 11,21,22 A recent population-based study from Germany showed that vaccination uptake is independently associated with perceived severity of influenza, perceived vaccination effectiveness, and perceived likelihood or severity of vaccination side effects, 9 whereas a study from Canada reported that knowledge plays a smaller role in the vaccination decision-making process than beliefs concerning risk perception and vaccination effectiveness. 23 Our study demonstrates that as knowledge increases, vaccination rates increase.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies performed on an elderly population (>65 years) in Turkey indicated that the minimal influenza vaccination rate in patients with COPD was 5.9% and the maximal rate was 27.3% (6). In another single-centre study, pneumococcal and influenza vaccination rates were 51% (7). …”
mentioning
confidence: 99%